BAHASA TAMTSÃL DALAM ALQURâÃN - Budiharjo, Budiharjo (Universitas Muhammadiyah Surakarta, 2006)
The language of âtamtsilâ is the part of Arabic literature. It uses exemplification about something with others in which it locates in the Qurâan. The language of âtamtsilâ in the Qurâan is divided into three parts: âal-amstal al-musharrohaâh, âal-amstal al-maknuunahâ, and âal âamstal al-mursalahâ. âAl-amstal al- musharrohahâ is the expression which is explained or stressed by the pronunciation of âmatsalâ. âAmtsal al-maknuunahâ is the exemplification which is not stated by âmatsal tamtsilâ. âAmtsal al-mursalahâ is the independent sentence which does not use the pronunciation of âtasybih clearlyâ; yet, this sentence has the function as âamtsalâ. The teachings in the form of âtamtsilâ which exist in the verses specifi- cally can also be classified into several parts, i.e: faith is theological matters, and moral in order to guide human being to have good behaviors, it is an abstract mate- rial which is described in the concrete form which could be felt and the mind can accept it easily.Â Key words: Al-QurâÃ¢n, bahasa tamtsÃ®l, arabic literature, tuntunan.Â